Pertumbuhan rumput jepang (Zoysia japonica) pada berbagai tingkat kemiringan dengan aplikasi Hydroseeding - Sri Sulastri; Anisa Zairina; Agus Sukarno; Diena Widyastuti (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
Research on Hydroseeding in Indonesia is still limited. The application of this hydroseeding technique can be developed for landslide management. This study aims to analyze the percentage of growth (viability) and growth of Japanese grass (Zoysia japonica) planted on landslide soil media at various levels of slope. This research was carried out at the Central Laboratory and greenhouse of the Malang Agricultural Institute in March – July 2020. The soil media used was obtained from landslides in Ngantang, Malang Regency. A total of 5 kg of media was put in a plastic box. Then the box is placed on a shelf with a slope of 30o, 50o, and 70o. Japanese Grass Seeds obtained from the market are mixed with compost, soil conditioner, guar gum, water to form a Hydroseeding formula. The formula is then sprayed onto the growing media. The results showed that the application of hydroseeding with Japanese grass seed (Z. japonica) on media placed with a slope of 70o could potentially be used as a formula for the revegetation process of landslide-affected land. The hydroseeding treatment at this slope resulted in the highest seed viability and growth rate. Thus, Japanese grass (Zoysia japonica) has the potential to be used as a pioneer plant in land reclamation.